Rencana Aksi Korporasi private placement yang Dilakukan oleh PT. SLJ GLOBAL, Tbk. terhadap CARRIEDO Limited - Alvianda, Arvi (Jurnal Suara Hukum, 2020)
One of the most important elements in the framework of the business development strategy of public companies (issuers) is the addition of capital. The addition of capital can be done in two ways, namely Capital Increase by providing Pre-emptive Rights and Capital Additions without Giving Pre-emptive Rights. Providing Rights is the same as Rights Issue, while without giving Rights can be equated with Private Placement. However, generally people are more familiar with calling private placement with the term Right Issue without Preemptive Rights. Arrangements regarding Preemptive Rights are regulated in POJK No.32/POJK.04/2015 concerning Addition of Company Capital By Providing Pre-emptive Rights, while without providing Preemptive Rights is regulated in POJK No.38/POJK.04/2014 concerning Capital Increase of Public Companies without Giving Pre-emptive Rights. The research method is used a normative juridical method. The research specifications are used descriptive-analytical. From the results of the study it can be concluded that the Capital Increase without Giving Preemptive Rights is carried out by PT. SLJ GLOBAL Tbk, by issuing new shares to creditors as a form of debt payment is one of the best ways for the Company. This method proved to be able to reduce debt and increase the paid up capital of the Company, as well as making the Creditor as a new shareholder. However, corporate action through the issuance of new shares without giving HMETD, so that there are additional new investors, resulting in a percentage share ownership of each of the existing shareholders has decreased. (Dilution).